Functional Genomic Analysis of Variation on Beef Tenderness Induced by Acute Stress in Angus Cattle. (12th April 2012) - Zhao, Chunping; Tian, Fei; Yu, Ying; Luo, Juan; Mitra, Apratim; Zhan, Fei; Hou, Yali; Liu, George; Zan, Linsen; Updike, M. Scott; Song, Jiuzhou
Abstract : Beef is one of the leading sources of protein, B vitamins, iron, and zinc in human food. Beef palatability is based on three general criteria: tenderness, juiciness, and flavor, of which tenderness is thought to be the most important factor. In this study, we found that beef tenderness, measured by the Warner-Bratzler shear force (WBSF), was dramatically increased by acute stress. Microarray analysis and qPCR identified a variety of genes that were differentially expressed. Pathway analysis showed that these genes were involved in immune response and regulation of metabolism process as activators or repressors. Further analysis identified that these changes may be related with CpG methylation of several genes. Therefore, the results from this study provide an enhanced understanding of the mechanisms that genetic and epigenetic regulations control meat quality and beef tenderness.